The effect of internal and external focus of attention on game performance in tennis - Marina Tsetseli; Eleni Zetou; Nikos Vernadakis; Maria Michalopoulou (Palacký University Olomouc, 2016)
Background: Great importance has been given in recent years to the impact of focus of attention cues during skills execution but not during real game play, where more cognitive skills are involved besides technical performance. Objective: The purpose of the present study was to examine the effect of internal and external focus of attention instructions on the components of the game performance (decision making, skill execution, base) in tennis. Methods: The participants (N = 60) were divided into three groups and followed an intervention training program that lasted 6 weeks; IF group (n = 20) under internal focus of attention instructions, EF group (n = 20) under external focus of attention instructions and CON group (n = 20) under no attentional focus instructions. Three measurements took place (pre, post and ret) in which the participants were recorded on video while playing matches in real scoring conditions. Game Performance Assessment Instrument (GPAI) was used to evaluate the components of game performance in tennis in three game situations; service, return of the service, base line game. Results: ANOVA repeated measures in a 3 (groups: IF, EF & CON) × 3 (measurements: pre, post, ret) revealed a significant interaction between groups and measurements and post hoc analysis indicated that the group that was instructed to focus externally improved significantly only in decision making compared to the internal focus of attention and to the control group. The score difference was maintained at the retention test as well, which indicates that the impact concerned not only performance but also learning. Conclusions: Instructions that aim to an external focus of attention enhance decision making skills, which are considered the most important element of game performance in tennis.